EFEKTIFITAS KEBIJAKAN STRUKTUR MODAL DALAM MENINGKATKAN NILAI PERUSAHAAN - Herry Subagyo (Jurnal Bisnis dan Ekonomi, 2011)
This study aims to create a model of the relationship of Capital structure policy with firmvalue is more consistent. This model puts the investment opportunity set as a moderating variablethat can strengthen or weaken the effect of funding policy to firm value. Sample used in this studyis companies incorporated in the manufacturing industry whose stock are actively traded on theIndonesia Stock Exchange. Data used is panel data, cross section data and time series data, theperiod 2004 to 2008. The results of this study found the effectiveness of the policy of capitalstructure is determined by Investment opportunity set. The use of debt will reduce firm value whenhigh investment opportunity set. When ivestment opportunity set is low, will enhance firmvalue. This findings indicate a tendency of overinvestment when high potential growth, whilecompanies low potential growth, debt can be used to control management not to overinvestment.Key Words: capital structure, firm value, investment opportunity set.